Development of EMG-FMG Based Prosthesis With PVDF-Film Vibrational Feedback Control - Choi, Yuna; Lee, Seulah; Sung, Minchang; Park, Junho; Kim, Sungmin; Choi, Youngjin (IEEE sensors journal, 2021)
The paper proposes an EMG-FMG-based prosthesis using a vibrational feedback method. The control loop for bio-feedback consists of a feed-forward loop for controlling the prosthetic hand and a sensory feedback loop for delivering the sense of vibration according to the distance with an object. In addition, the motion of the prosthetic hand using the EMG-FMG knit band sensor as an input device is generated via a decision tree algorithm, the distance is measured using a capacitive knit data glove, and the vibrational feedback using a PVDF piezoelectric actuator is provided. The control loop for bio-feedback was verified experimentally. First, the performance of the sensors and control methods was analyzed, and the results of EMG-FMG motion recognition and vibrational feedback were verified. Second, the experiment was conducted on ten subjects who wore prosthesis to which the bio-feedback method was applied. Thanks to the control loops for bio-feedback, the grasping time with blindfolded was reduced by 2.92 seconds and the number of failures decreased by 1.04 times. As a result, it was confirmed that the control loop for bio-feedback could improve the performance of the prosthesis.